2012
DOI: 10.1016/j.cmet.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hepatic Synthesis and Dysregulation of Cholesterol Metabolism Is Associated with the Severity of Nonalcoholic Fatty Liver Disease

Abstract: SUMMARY Nonalcoholic fatty liver disease (NAFLD) is associated with increased cardiovascular and liver-related mortality. NAFLD is characterized by both triglyceride and free cholesterol (FC) accumulation without a corresponding increment in cholesterol esters. The aim of this study was to evaluate the expression of cholesterol metabolic genes in NAFLD and relate these to disease phenotype. NAFLD was associated with increased SREBP-2 maturation, HMG CoA reductase (HMGCR) expression and decreased phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

38
453
1
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 552 publications
(504 citation statements)
references
References 39 publications
(50 reference statements)
38
453
1
12
Order By: Relevance
“…16 In NAFLD, liver steatosis is associated with increased cholesterol synthesis and decreased cholesterol absorption. 17 Interestingly, triglyceride accumulation alone may not induce liver injury or inflammation, 18,19 whereas the accumulation of free cholesterol [20][21][22] and the dysregulation of the cholesterol synthesis pathway 23 relates to NASH.…”
mentioning
confidence: 99%
“…16 In NAFLD, liver steatosis is associated with increased cholesterol synthesis and decreased cholesterol absorption. 17 Interestingly, triglyceride accumulation alone may not induce liver injury or inflammation, 18,19 whereas the accumulation of free cholesterol [20][21][22] and the dysregulation of the cholesterol synthesis pathway 23 relates to NASH.…”
mentioning
confidence: 99%
“…The roles of both triglycerides and free fatty acid accumulation in NAFLD have been elucidated in many studies 5 . By contrast, the role of cholesterol in NAFLD has been less extensively studied but is gaining increasing attention 1,[6][7][8] .…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that cholesterol metabolism and trafficking might play an important role in the pathogenesis of NAFLD and NASH 1 . Cholesterol is highly enriched in LDLs and is taken up by the liver via receptor-mediated endocytosis of the LDL-LDL receptor complex at the plasma membrane.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14,36 Notably, miR-34a has been shown to be up-regulated in both human serum 50,51 and liver in humans and animal models of NAFLD. 14,55,121,122 Two recent studies suggest two differing mechanisms for the involvement of miR-34a in NASH pathogenesis through down-regulation of SIRT-1; a) leading to AMP kinase dephosphorylation and subsequent decreased phosphorylation of HMGCoA, ultimately leading to cholesterol accumulation 121 ; b) increased acetylation of p53 causing activation of apoptosis. 123 MiR-122 is significantly down-regulated in humans and animal models of NAFLD patients.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%